Zastosowanie wybranych metod scoringowych do oceny kondycji finansowej przedsiębiorstw na przykładzie branży cukierniczej - Czarny, Anna (Application of Selected Scoring Methods in the Assessment of the Financial Condition of Enterprises on the Basis of the Confectionery Industry, 2006)
Scoring methods, along economic indicator analyses, are increasingly frequently used in the assessment of the financial condition of enterprises. The methods consist in deriving a single synthetic indicator, which adequately differentiates between enterprises in good and bad financial condition. In order to ensure proper assessment of an enterprise, the applied scoring methods should be developed and implemented in the country they pertain to. Their proper selection and adequate interpretation is of utmost importance here.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 132-141